BESPALOFF, Rachel: De la Ilíada, Edición, traducción e introducción de Rosa Rius Gatell, Lleonard Muntaner, Palma (Mallorca), 2012 - Llorca Morell, Blanca (Daimon Revista Internacional de Filosofia, 2013)
Reseña de este libro.